Prevalence and sociodemographic correlates of routine breast cancer screening practices among migrant‐Australian women - Michelle Lam; Cannas Kwok; Mi‐Joung Lee (Elsevier, 2018)
Abstract Objective: To evaluate breast cancer screening (BCS) practice and explore the relationship between sociodemographic factors and breast awareness (BA), clinical breast examination (CBE) and mammography in migrant‐Australian women. Method: Secondary analysis was performed on the pooled sample (n=1,744) from five cross‐sectional studies of BCS rates among immigrant‐Australian women, and the associated sociodemographic factors. Results: Only 19% of women participated in routine BA, 27.4% of women in the target group of >40 year presented for an annual CBE, and 60.6% of women in the target group of 50-74 years received a biennial mammogram. Associated sociodemographic factors differed by modality except for length of Australian residency. In multivariable analysis, age, length of Australian residency, marital status, and employment status accounted for more than 50% of the variance in regular BA and CBE. Conclusion: These findings indicate suboptimal BCS rates persist among migrant‐Australian women, and suggest the importance of certain sociodemographic factors in BCS practice. Implications for public health: Further education is required for BA and CBE practice in immigrant‐Australian women, especially for those who have resided in Australia less than 12 years without a partner.